The feasibility of an innovative online mind-body wellness program for medical students (Canadian Medical Education Journal, 2025)
Purpose: Medical students have higher stress levels than their age-matched peers; however, few online wellness interventions have been trialed in this population. This pilot study examined the feasibility of an online wellness program for medical students. Method: This was a pilot feasibility, mixed-methods study with a pre-post design. From September to October 2020, medical students from a large Canadian medical school were introduced to a 12-week online program with weekly sessions on yoga, breathwork, meditation, and nutrition. Feasibility measures included adherence, satisfaction, and retention, with secondary outcome measures including stress, anxiety, quality of life, and mindfulness. Post-program qualitative interviews explored participant experience. Results: Of 74 participants, 64 completed the program. Twenty-one achieved the program goal of participating at least two days per week. While 74.8% of participants found the program accessible and satisfying, some students reported challenges with adherence. Exploratory analysis indicated there are signals for reduced stress (11%, p = 0.005), anxiety (14%, p = 0.001), and improved mindfulness (5.6%, p = 0.001). Qualitative analysis revealed themes of participants experiencing an increased sense of balance and mindfulness. Conclusion: A 12-week online wellness intervention appears feasible for medical students, showing potential benefits for stress, anxiety, and mindfulness.